Kinerja Struktur Modal Terhadap Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia - Pandu Adji Bramasta; Deni Ramdani (Lembaga Pengembangan Kinerja Dosen, 2023)
The pharmaceutical sub-sector company is one of the sectors that have benefited from the Covid-19 pandemic that occurred in early 2019 until now. Due to the Covid-19 pandemic, it has an impact on public health. This article aims to provide empirical evidence related to the capital structure with the object of this research being companies in the pharmaceutical sub-sector listed on the Indonesia Stock Exchange for the period 2019-2021. The data used are quantitative data obtained from the Indonesia Stock Exchange or Indonesia Stock Exchange. The secondary data used for this research is the company's financial statements on the Indonesia Stock Exchange. A higher DER means that the company's financial performance is not good because the more it uses debt which allows it to go bankrupt if the company is unable to pay its obligations. also increase the existing assets in the company. ROA states that the greater the ROA owned by a company, the bigger the company is.